Comparison of Taurine and Metformin on Paraoxonase Enzyme Activity and Lipid Profiles in Streptozotocin-Induced Diabetic Rats - rahimian , Elham; Golbashirzadeh, Morteza; Moradzadegan , Atousa (Iranian Journal of Pharmaceutical Sciences, 2026)
Diabetes remains a pressing global health challenge, demanding innovative biochemical interventions for effective management. This study evaluates the effects of taurine and metformin on glucose regulation, lipid metabolism, and antioxidant enzyme activity in diabetic rats. Diabetes was induced in mice using a single intraperitoneal dose of streptozotocin (60 mg/kg), and animals with blood glucose levels exceeding 300 mg/dL were considered diabetic. The experimental subjects were systematically classified into four groups: healthy controls, diabetic controls, metformin-treated diabetics, and taurine-treated diabetics. Metformin and taurine were each administered via oral gavage at a dosage of 500 mg/kg/day for a period of one month, beginning seven days post-diabetes induction. Key indicators assessed included changes in body weight, fasting glucose levels, serum lipid components, and paraoxonase enzymatic activity. Metabolic evaluations included fasting blood glucose, body weight, lipid profile parameters, and paraoxonase enzyme activity. Metformin treatment did not significantly alter weight relative to the diabetic group, whereas taurine led to a notable improvement. Hyperglycemia was markedly reduced in both treatment groups compared to diabetic controls. Furthermore, analysis of lipid components revealed significant normalization: triglyceride, cholesterol, and LDL levels decreased, while HDL concentrations increased with both interventions. Antioxidant assessment showed restored paraoxonase activity in taurine- and metformin-treated animals. These outcomes support the hypothesis that taurine and metformin contribute to the restoration of biochemical equilibrium in diabetic conditions. Both Taurine and metformin can modulate Diabetes-related metabolic disturbances, aiding in physiological stabilization. Both agents promoted glycemic correction, lipid improvement, and enzymatic recovery. Their efficacy suggests promise in supportive metabolic care for diabetes.